Yeast prions and protein chaperones - Masison, Daniel (Henry Stewart Talks, 2008)
Role of protein chaperones in protein folding, Yeast prions as amyloid forms of cellular proteins, Requirement of chaperone machinery for prion propagation, Chaperone mutants adversely affect prions and provide insight into chaperone/amyloid interactions
Archived at 2021/02/25